2013
DOI: 10.1155/2013/637513
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-15 (IL-15) and Anti-C1q Antibodies as Serum Biomarkers for Ectopic Pregnancy and Missed Abortion

Abstract: Given the present lack of clinically useful tests for the accurate diagnosis of ectopic pregnancy (EP), there is a need to select out those immunological factors measured in the maternal serum, as potential biomarkers. Our assumption was that C1q/anti-C1q antibody complexes and serum levels of interleukin-15 (IL-15) may play a role in differentiating abortions (MAs) and EPs and normal pregnancies. We assessed whether their measurement could set the diagnosis in a case control study at 6–8 weeks consisting of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Pregnancy is a period of evolving immunotolerance leading to changes in many immune mechanisms which influence (suppress or trigger) different types of AITD , and the course of systemic autoimmune diseases is also altered . We therefore speculate that pregnancy might be a trigger for increased anti‐C1q production, which may, on one hand, even be protective on the course of pregnancy as suggested by the data of Daponte , but on the other hand may be pathogenic with regard to the development of AITD.…”
Section: Discussionmentioning
confidence: 85%
“…Pregnancy is a period of evolving immunotolerance leading to changes in many immune mechanisms which influence (suppress or trigger) different types of AITD , and the course of systemic autoimmune diseases is also altered . We therefore speculate that pregnancy might be a trigger for increased anti‐C1q production, which may, on one hand, even be protective on the course of pregnancy as suggested by the data of Daponte , but on the other hand may be pathogenic with regard to the development of AITD.…”
Section: Discussionmentioning
confidence: 85%
“…Studies based on these observations have measured the levels of antibodies to C1q complement in early pregnancy failure have been conducted. Daponte et al failed to observe any difference between normal viable IUP, EP and other abnormal IUP [116]. As new studies would be undertaken by different groups, more information regarding this marker is likely to emerge.…”
Section: Antibodies To C1q Complementmentioning
confidence: 97%
“…IL-15 has also been studied as it is expressed by human placental tissue culture and it is maximally expressed during the implantation period in the deciduas. Daponte et al reported that IL-15 concentrations were significantly higher in women with EP compared to patients with IUP, and found IL-15 to have high diagnostic accuracy for the discrimination of a viable IUP from an EP with an area under the curve of 0.818 [116].…”
Section: Circulating Cytokinesmentioning
confidence: 99%
“…C1q deficiency is associated with improper placental formation, trophoblast invasion, impaired angiogenic balance and an increased risk of fetal death resulting in miscarriages, preterm delivery, and PE (Agostinis et al, 2010;Singh et al, 2011). Lower concentration of anti-C1q antibodies and higher levels of IL-15 have been observed in ectopic pregnancies and missed abortions when compared to complicated pregnancies (Daponte et al, 2013). Storelli et al have reported that mothers exposed to polychlorinated biphenyls (PCBs) are at a higher risk of spontaneous miscarriage, stillbirth and fetal resorption (Storelli et al, 2011).…”
Section: C1qmentioning
confidence: 99%